Evolutionary Conservation and Diversity of Interspecific and Intraspecific Callophylaceae Chloroplast Genomes - Nguyen, Nhat Nam; Do, Hoang Dang Khoa (HAYATI Journal of Biosciences, 2026)
The chloroplast genome (cpDNA) plays an important role in the evolutionary history of various plant species. However, most records of cpDNA focused on a representative of a plant taxon. How are interspecies and intraspecies cpDNA evolutionary patterns? To provide hints for this question, we conducted comparative genomic analyses of genome size, structure, gene content, and sequence variations among examined Calophyllaceae interspecific and intraspecific cpDNAs. The results indicated a conservation of genome structure and gene content in both interspecies and intraspecies groups. Within the intraspecies group, Calophyllum inophyllum had a stable genome size and high pairwise identity (99.998%) compared to a variable genome size (from 161,444 bp to 161,473 bp) and pairwise identity (from 99.7% to 99.98%) of Mesua ferrea. Consequently, M. ferrea cpDNA has higher single-nucleotide polymorphism sites and indels compared to C. inophyllum. Otherwise, interspecies cpDNAs exhibited a diversity of genome size and different sequence variation rates between Calophyllum and Kielmeyera species. Comparative genomic analyses revealed conserved and diverse patterns during the evolutionary history of interspecies and intraspecies Calophyllaceae cpDNAs.